Continuous output integral sliding mode control for switched linear systems. (November 2016) - Galván-Guerra, R.; Fridman, L.; Velázquez-Velázquez, J.E.; Kamal, S.; Bandyopadhyay, B.
Abstract: A continuous output integral sliding mode robustification methodology for switched uncertain linear time invariant systems with state-dependent location transitions and dwell time is presented. The robustifying methodology is based on the adjustment of the super-twisting algorithm gains to assure the convergence time and the attenuation of the chattering. The use of the adjusted STA allows to reconstruct the states theoretically exactly before half of the dwell time without the usage of filters, via a continuous cascade observer. Moreover, it allows to generate a continuous control signal that is turn on after the observer has converged, guaranteeing theoretically exact compensation of the matched uncertainties/perturbations before the dwell time.